morpho-lexical analysis for printed Arabic words using c - Ghaydaa AbdulAziz Altalib; Mahir Ahmad Anwar Alnaema; Rafida Hameed Altaee (College of Education for Pure Sciences, 2010)
ABSTRACT In this research we propose a statistical method and morpho-lexical analysis for correcting Arabic words as a post processor for Arabic words output from OCR systems. Dictionaries of words were built for the comparison to the attached word. The present research uses multiple knowledge sources and basing on the Arabic language properties, statistical method, morpho-lexical analysis and dictionary look-up for error detection and correction. Correction of errors in this research depends on the type of possible error, which can be: transposing two adjacent letters, rejection, replacing an incorrect letter, inserting a missing letter, substitution errors, which are most frequently committed by the OCR systems.